2018
DOI: 10.1111/ijpp.12489
|View full text |Cite
|
Sign up to set email alerts
|

Do pharmacists contribute to patients’ management of symptoms suggestive of cancer: a qualitative study

Abstract: Objectives Limited awareness of cancer symptoms results in patient delay in seeking help and contributes to delay in diagnosis. Few UK studies have investigated the potential for community pharmacists to facilitate earlier detection of cancer. This study aimed to investigate what actions patients take to manage their early cancer symptoms, to identify the extent of current community pharmacy involvement and to consider the potential role for community pharmacists to facilitate appropriate management and apprai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
(73 reference statements)
1
4
0
Order By: Relevance
“…A previous qualitative study with patients diagnosed with lung, colorectal or gastro-oesophageal cancer found that half of the patients had initially tried to manage red flag symptoms by purchasing OTC medication prior to diagnosis. 18 This work supports the findings of our study, highlighting potential opportunities to use community pharmacies in earlier identification of suspicious symptoms. This study, however, found that frequent purchases of the same medication were not explored fully, highlighting the potential for patients with ongoing symptoms to be missed.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A previous qualitative study with patients diagnosed with lung, colorectal or gastro-oesophageal cancer found that half of the patients had initially tried to manage red flag symptoms by purchasing OTC medication prior to diagnosis. 18 This work supports the findings of our study, highlighting potential opportunities to use community pharmacies in earlier identification of suspicious symptoms. This study, however, found that frequent purchases of the same medication were not explored fully, highlighting the potential for patients with ongoing symptoms to be missed.…”
Section: Discussionsupporting
confidence: 90%
“…This work supports the findings of our study, highlighting potential opportunities to use community pharmacies in earlier identification of suspicious symptoms. This study, however, found that frequent purchases of the same medication were not explored fully, highlighting the potential for patients with ongoing symptoms to be missed 18. Several small-scale pilots have also found that pharmacist integration into lung cancer referral pathways is both feasible and acceptable, resulting in high-quality referrals 19 20.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A 2015 systematic review examining factors influencing timeliness of help seeking for possible cancer symptoms, found that awareness of possible cancer symptoms is lower among more deprived populations, who also take longer to present to medical services when they have symptoms 12. Such people may instead seek advice or over-the-counter treatments for problems like cough or indigestion,1314 leading policy makers to believe that “pharmacies are well placed to spot people presenting with ‘red flag’ potential cancer symptoms.”15…”
Section: What Is the Rationale For Involving Community Pharmacy?mentioning
confidence: 99%
“…One small qualitative study found that more than half of 25 patients diagnosed with lung, colorectal, or gastro-oesophageal cancer had initially tried to manage their red flag symptoms by purchasing over-the-counter (OTC) medication prior to diagnosis; only three participants sought help from pharmacy staff, from whom they received appropriate advice. 12 The study identified that frequent purchases of the same medication were not explored further by staff in the community pharmacy, and participants had low awareness of the pharmacists’ healthcare advisory role. One other study focused on patients seeking advice or OTC medication for red flag symptoms.…”
Section: Do Patients Present To Community Pharmacists With Potential ...mentioning
confidence: 99%